Acute alcohol effects on neuronal and attentional processing: striatal reward system and inhibitory sensory interactions under acute ethanol challenge - Schreckensberger, M; Amberg, R; Scheurich, A; Lochmann, Matthias; Tichy, W; Klega, A; Siessmeier, T; Gründer, G; Buchholz, Hans-Georg; Landvogt, C; Stauss, J; Mann, K; et al. (Neuropsychopharmacology, 2004)
The acute influence of ethanol on cerebral activity induces complex psycho-physiological effects that are considerably more pronounced during acute ethanol influx than during maximal blood alcohol concentration (elimination phase). Despite the psychiatric and forensic relevance of these different ethanol effects, the underlying neuronal mechanisms are still unclear. In total, 20 male healthy volunteers were investigated each with three different experimental conditions in a randomized order using an intravenous ethanol challenge (40 g bolus infusion): during influx phase, elimination phase, and under placebo condition. During and after the ethanol (or placebo) infusion, neuropsychological testing of divided attention for visual and auditory stimuli was performed with subsequent 18-FDG PET acquisition. The PET data were analysed using SPM99. Ethanol influx and elimination phase showed focal activations in the bilateral striatum and frontal cortex and deactivations in the occipital cortex. The comparison of influx phase vs elimination phase revealed activations in the anterior cingulate and right prefrontal cortex, relevant deactivations were found in the left superior temporal cortex including Wernicke's area. Neuropsychological testing showed an attentional impairment under ethanol influx compared to ethanol elimination and placebo with an inverse correlation of the attentional performance for auditory stimuli to occipital activity and for visual stimuli to the left temporal (including auditory) cortex. Acute ethanol administration in healthy volunteers stimulates those striatal regions that are considered to have a particular relevance for alcohol craving ('reward system'). Modality specific reciprocal inhibition of sensory cortex activity seems to be relevant for attentional performance during acute alcohol impact.
UnivIS-Import:2015-03-09:Pub.2004.phil.dps.iss.pspbio.acutea
Keywords: 18-FDG; Alcohol; Attention; Ethanol; Imaging; Occipital; PET; Striatum